Digital agriculture in action: Selected case studies from India - Dixit, Sreenath; Dhulipala, Ram; Sylvester, Gerard; Mothkoor, Venugopal; Koganti, Dharani Kanth (Food and Agriculture Organization of the United Nations, 2022)
Agriculture is becoming more knowledge-intensive. Access to timely, accurate information tailored to specific locations and conditions is critical to helping farmers make the most of their resources in changing circumstances. Digital technologies help overcome these challenges by bridging the information gap, improving access to market information, enhancing access to micro-finance, providing actionable advisories on managing pest and disease as well as improving agriculture human capital. However, sustaining digital interventions needs a holistic approach that includes the right policies, frameworks, ecosystem and capacities. This publication highlights some successful initiatives in leveraging digital technologies, improving value-chain processes and building capacity to bring about positive change among agriculture stakeholders and improve livelihoods. This publication is part of the Country Investment Highlights series under the FAO Investment Centre's Knowledge for Investment (K4I) programme.